2014
DOI: 10.3168/jds.2013-7164
|View full text |Cite
|
Sign up to set email alerts
|

Addition of potassium carbonate to continuous cultures of mixed ruminal bacteria shifts volatile fatty acids and daily production of biohydrogenation intermediates

Abstract: A recent study reported a 0.4 percentage unit increase in milk fat of lactating dairy cattle when dietary K was increased from 1.2 to 2% with potassium carbonate. Because milk fat yield has been associated with ruminal production of certain conjugated linoleic acid (CLA) isomers, 2 studies were conducted to determine if increasing potassium carbonate in the rumen would alter patterns of fermentation and biohydrogenation. In experiment 1, 5 dual-flow continuous fermenters were injected just before each feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…In the present study, pH of the CON fermenters was well below 5.5 and the average extent of biohydrogenation of C 18:2 in CON fermenters (expressed as mg of outflow per 100 mg of input) was 68.7%. This is comparable to Jenkins et al (2014) , who reported average C 18:2 biohydrogenation of 72%; however, pH in that study averaged 6.0. This indicates that in spite of low culture pH in the present study, biohydrogenation extent remained high.…”
Section: Resultssupporting
confidence: 83%
“…In the present study, pH of the CON fermenters was well below 5.5 and the average extent of biohydrogenation of C 18:2 in CON fermenters (expressed as mg of outflow per 100 mg of input) was 68.7%. This is comparable to Jenkins et al (2014) , who reported average C 18:2 biohydrogenation of 72%; however, pH in that study averaged 6.0. This indicates that in spite of low culture pH in the present study, biohydrogenation extent remained high.…”
Section: Resultssupporting
confidence: 83%
“…These previous studies manipulated the DCAD value via the addition of cation or anion sources to the diet fed, potentially affecting rumen fermentation. Iwaniuk and Erdman (2015) reported a positive linear relation between the DCAD value and ruminal pH and the molar proportions of acetate and butyrate, all of which have been associated with increased milk fat content (Kolver and de Veth, 2002;Jenkins et al, 2014). In the current study, however, the DCAD value of the basal diet was similar for all treatments, and NH 4 Cl was infused into the abomasum, preventing effects at the rumen level and its consequences downstream on milk fat synthesis.…”
Section: Effects Of Abomasal Nh 4 CL Infusion and Associated Metabolic Acidosismentioning
confidence: 49%
“…They suggested that K 2 CO 3 promotes the predominant trans-11 biohydrogenation pathway rather than the trans-10 pathway in the rumen. In the current experiment, milk fat concentration of trans-10 18:1, which can be used as a marker for milk fat depression (Jenkins et al, 2014), was increased by 73% when cows received SBO as compared with unsupplemented cows (Table 5). However, in contrast with Ma et al (2017), dietary K 2 CO 3 did not affect milk fat concentration of trans-10 18:1, or any other identified FA biohydrogenation intermediates.…”
Section: Milk Production and Compositionmentioning
confidence: 59%
“…Previous research suggests that the decrease in milk fat synthesis observed in dairy cows fed high-concentrate diets can be alleviated by increasing DCAD and dietary K concentration (Harrison et al, 2012). Using continuous fermenters, Jenkins et al (2014) evaluated the effect of 3 levels of added K in the form of K 2 CO 3 with 2 concentrations of soybean oil (SBO, 0 or 3.4% of DM) on ruminal biohydrogenation of fatty acids (FA). The authors reported that the addition of K 2 CO 3 alone or with SBO increased 18:0 and cis-9,trans-11 18:2, whereas daily outflow of trans-10 18:1 and trans-10,cis-12 18:2 was decreased.…”
Section: Introductionmentioning
confidence: 99%